2021
DOI: 10.2991/ahsr.k.210115.115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Active Learning and FGD Education Methods on the DAGUSIBU Knowledge of MA Nurul Ummah Students, Yogyakarta

Abstract: A research on drugs administration in Manado in 2014 revealed that 44.77% of the local population did not procure drugs properly, 75.9% received the wrong ones, 25.3% did not store them as suggested, and 72% did not use them appropriately. As an attempt to avoid medication management mistakes in the community, the Indonesian Pharmacist Association has introduced a program termed DAGUSIBU, an abbreviated form of 'to get, use, store, and discard'. DAGUSIBU contains information on the procedures to receive, use, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Therefore, it can be concluded that there had a significant influence on the management of Clitoria ternatea and Psidium guajava L. The FGD method allows active participation of participants and provides them with an opportunity to discuss their opinions and share experiences with other participants. Therefore, by utilizing the advantages of the FGD education method, respondents find it easier to accept the information provided and enhance their knowledge (Candradewi et al, 2021). The process of changing one's knowledge is accomplished through input approaches involving human, technical, and financial resources.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it can be concluded that there had a significant influence on the management of Clitoria ternatea and Psidium guajava L. The FGD method allows active participation of participants and provides them with an opportunity to discuss their opinions and share experiences with other participants. Therefore, by utilizing the advantages of the FGD education method, respondents find it easier to accept the information provided and enhance their knowledge (Candradewi et al, 2021). The process of changing one's knowledge is accomplished through input approaches involving human, technical, and financial resources.…”
Section: Resultsmentioning
confidence: 99%
“…Metode intervensi ini berdasarkan pada proses belajar mandiri, yaitu terdiri dari fasilitator, narasumber dan para peserta (Suryawati, 2012). Jika dibandingkan dengan metode Focus Group Discussion (FGD), metode CBIA secara signifikan dapat meningkatkan pengetahuan lebih baik (p= 0,000) (Candradewi et al, 2021).…”
Section: Gambar 4 Pemberian Materi Oleh Narasumberunclassified